2006
DOI: 10.1098/rspb.2005.3420
|View full text |Cite
|
Sign up to set email alerts
|

Separate attentional resources for vision and audition

Abstract: Current models of attention, typically claim that vision and audition are limited by a common attentional resource which means that visual performance should be adversely affected by a concurrent auditory task and vice versa. Here, we test this implication by measuring auditory (pitch) and visual (contrast) thresholds in conjunction with cross-modal secondary tasks and find that no such interference occurs. Visual contrast discrimination thresholds were unaffected by a concurrent chord or pitch discrimination,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
153
6
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(186 citation statements)
references
References 62 publications
23
153
6
2
Order By: Relevance
“…We manipulated the allocation of voluntary attention using a single/dual task paradigm. This paradigm has been extensively used to investigate the involvement of attention in various visual processes as diverse as motion processing (Thiele et al 2002;Thornton et al 2002), stimulus localization (Adam et al 2008), contrast discrimination (Huang and Dobkins 2005;Alais et al 2006) and contextual modulation (Zenger et al 2000). Attention is a broad term covering a wide range of cognitive processes (Knudsen 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We manipulated the allocation of voluntary attention using a single/dual task paradigm. This paradigm has been extensively used to investigate the involvement of attention in various visual processes as diverse as motion processing (Thiele et al 2002;Thornton et al 2002), stimulus localization (Adam et al 2008), contrast discrimination (Huang and Dobkins 2005;Alais et al 2006) and contextual modulation (Zenger et al 2000). Attention is a broad term covering a wide range of cognitive processes (Knudsen 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Two alternative theories, which look at how our attentional capacity can affect perception, have been developed: the central and divided attentional resources theories [2,30,11,6,27,1,7]. Some models of attention claim that our attention operates on a global level and that is divided across multiple senses.…”
Section: Auditory-visual Cross-modal Interaction Research In Psychologymentioning
confidence: 99%
“…Based on these findings, Adcock et al proposed the existence of different specialized information processing systems in the human brain involved in multitasking. This view of independent processing resources, and these two examples of studies (Adcock, Constable, Gore, and Goldman-Rakic, 2000;Alais, Morrone, and Burr, 2006), may not be considered to be entirely consistent with the widespread views about processing resources and performance in dual tasks. Navon (1985) proposed another view on performance in two (or more) concurrent tasks in addition to his view about the number of resources available in concurrent tasks.…”
Section: The Cognitive Aspects Of Dual-processing Tasksmentioning
confidence: 86%
“…The second possibility is that performing one task has no bearing on the performance of the second task, suggesting that the resources used in the two tasks may be independent of one another (Kahneman, 1973;Keele, 1973;Kerr, 1973;Wickens, 2002). A study by Alais, Morrone, and Burr (2006) showed independence of resources for vision and audition when dual tasks contained dual-processing of these two different modalities. They used a visual contrast discrimination task and an auditory tone pitch discrimination task as the two concurrent tasks and found no effect on the performance of each task in the presence of the other.…”
Section: The Cognitive Aspects Of Dual-processing Tasksmentioning
confidence: 99%